Risk Assessment and Treatment Guide for Obstetric Thromboprophylaxis: Comprehensive Review of Current Guidelines - Eubanks, Allison A.; Deering, Shad H.; Thiel, Lisa M. (American Journal of Perinatology, 2019)
Objective Currently, there are numerous recommendations and often conflicting guidance provided for venous thromboembolism (VTE) prophylaxis in pregnancy. Our objective was to create a one-page risk assessment and treatment guide based on a review of the most recent and evidence-based publications on this subject to simplify the approach and allow all obstetric patients to be properly assessed for risk of VTE and treated if indicated.Study Design We identified studies by completing a PubMed and MEDLINE search from January of 1980 through March 2017 with articles utilizing a specific combination of the selected general keywords (thrombophilia, pregnancy, VTE, prophylaxis, hypercoagulability, antepartum, postpartum, risk, etc.). We completed the search at the saturation point, meaning that all combinations of the relevant words were directing us to the same articles. After collecting the relevant sources and reviewing them, a total of 10 articles/guidelines were selected for inclusion in the analysis.Results We outlined every recommendation in the identified articles and guidelines and included any recommendation that was cited in at least three different sources in the final guide. We used American College of Obstetrics and Gynecology recommendations as the base for screening and dosing guidelines and utilized known and published absolute risk values and odds ratios to stratify risk factors. This stratification was used for both antepartum and postpartum recommendations and a single-page guideline was created.Conclusion This compilation of guidelines integrates the complicated topic into a simple comprehensive guide where women can be identified early and accurately for appropriate VTE prophylaxis to protect them during and after pregnancy.
Keywords: venous thromboprophylaxis; pregnancy; venous thromboembolism; hypercoagulability; enoxaparin; heparin